Social Media Dependency and Information Privacy Concerns on Switching Behavior TikTok Users of Indonesian - Putri Rif'da Azmi Azahra; Marheni Eka Saputri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine switching behavior among users through the level of dependence and concern on social media over a long period. The objects used are TikTok social media users in Indonesia. Data collection for this study is conducted through the utilization of a questionnaire. The data was analyzed using multiple regression analysis with SPSS 25. Based on the results of multiple regression analysis, social media dependency and information privacy concerns have an impact on switching behavior on social media TikTok in Indonesia, only able to explain as much as 12.4%